From Research Ethics to Researching Ethics in an Online Specific Context - Östman Sari; Turtiainen Riikka (Cogitatio Press, 2022)
Along with the rise of a research field called digital humanities, online specific research ethics plays an especially significant role. Research on the same (Internet related) topic is usually multidisciplinary, and understanding research ethics even inside the same research community may vary essentially. It is important to recognise and pay attention to online specific contexts as well as the researcher’s own disciplinary background. In this empirical research paper, we will first sum up our previous work. Currently, we are working on a model which will help in positioning multidisciplinary researchers as ethical actors based on their research topics and backgrounds. In this article, we will present this model with a demonstration of the empirical data collected as part of a Finnish research project called Citizen Mindscapes, which concerns the cultures and history of Finnish discussion forums. We argue that in Finland, and probably also worldwide, online research ethics is in a phase where the focus should be moving from defining the ethical guidelines to studying research ethics as such. We will also discuss how the model will be further developed in an in-depth empirical process.